Frequency of diagnostic dilemmas in 131I whole body scanning - Leitha, Th.; Staudenherz, A. (Nuklearmedizin - NuclearMedicine, 2003)
Aim: The specific excretion pathways of iodine may cause several diagnostic pitfalls. Information concerning their relative frequency and possible consequences in daily routine is scarce. Methods: A total of 500 131I whole-body scans from 300 consecutive patients with differentiated thyroid cancer of two centers were analyzed. The reports were validated with other diagnostic findings during follow-up for 12 to 85 months. 126 scans (25.2%) were performed at the time of discharge after high dose 131I therapy (2960-11100 MBq). Residual activity was approximately 185 MBq 131I at the time of imaging. 374 scans (74.8%) were performed in ambulatory patients 48 h after oral administration of 74 MBq131I. All patients revealed TSH concentrations >35 U/ml. Results: A computerized literature search revealed 74 entities that may cause a false-positive whole body scan, from which 12 were present in our cohort. The uptake patterns could be epitomized into nine clinical settings. Apart from the significantly higher frequency of cervical activity in residual thyroid tissue in patients after high dose therapy no statistically significant difference was found between high and low dose patients. The most frequent combination was stomach and colon activity, which was seen in 15.3% of all scans. Additional images or diagnostic procedures were necessary in 59.3%. Only one patient with a kidney metastasis was initially misinterpreted. The major clinical problems included: contamination, superimposed intestinal retention, hot nose, isolated peripheral metastasis, unexpected breast activity and kidney metastasis. Conclusion: 131I whole-body scanning has to be performed with painstaking precision and full awareness of even the rarest pitfalls in order to remain a sensitive and specific technique for diagnosing metastases from differentiated thyroid carcinoma.
Keywords: 131I; whole-body scan; differentiated thyroid cancer